Impact of Farmland Rental Contract Disputes on Farmland Rental Market Participation - Xingguang Li; Xuexi Huo (Land, 2022)
In the context of an ambiguous structure of farmland property rights, farmland rental contract disputes exhibited an upward tendency over the past decade, in practice, which damaged the expectations of land tenure security and, consequently, influenced the willingness of people to participate in farmland rental markets. Thus, the main aim of this paper was to analyze the impact of farmland rental contract disputes on farmland rental market participation, which was empirically tested by using a logit model, IV-probit model, and survey data for 762 apple growers. The results indicated that (1) farmland rental contract disputes significantly boosted the transfer of farmland to relatives and friends, (2) obtaining reasonable compensation in the process of solving farmland rental contract disputes significantly boosted farmland rental market participation for all types of objects of farmland transfers, and (3) farmland rental contract disputes significantly promoted farmers’ choice of relatives as the objects of farmland transfers. Participating in farmland rental markets was a freely pursued decision-making process, based on the actual situation, and farmers improved their expectations of the risks to farmland property rights by resorting to the reputation mechanism. However, obtaining reasonable compensation was conducive to reducing market segmentation and discrimination. Based on our analysis, the key factor in enhancing farmland rental market participation and reducing market segmentation was improving the stability of farmland property rights, and, in practice, farmland rental contract disputes should be reasonably reduced and regulated. This paper not only emphasizes the importance of solving farmland rental contract disputes reasonably, but also provides a reference for improving relevant laws and regulations on farmland transfers, which is conducive to developing farmland rental markets in the context of an ambiguous structure of farmland property rights in some developing countries.